Distribution and timing of nesting in Hawaiian Geese in relation to food phenology in scrublands. - Woog, Friederike (Wildfowl, 2014)
The seasonal distribution patterns of individually marked Hawaiian Geese or Nene Branta sandvicensis are described in relation to the availability of their food plants in scrubland. The phenology of the most important plant groups was recorded over a 18 month period, and goose numbers and nesting activity monitored. Plant phenology varied considerably between species, between sites and with elevation. Geese appeared to time their movements and nesting according to local food availability. The analyses of a long-term database on nest records (1960 -1996), revealed that peak nest initiation was in November and December, coincident with high average rainfall. Generally, geese that nested earlier in the season, when berry availability was high, were more successful in rearing young, but other events such as predation,